Variants of opioid system genes are associated with non-dependent opioid use and heroin dependence - Randesi, Matthew (Drug Alcohol Depend, 2016)
BACKGROUND: Heroin addiction is a chronic, relapsing brain disease. Genetic factors are involved in the development of drug addiction. The aim of this study was to determine whether specific variants in genes of the opioid system are associated with non-dependent opioid use and heroin dependence. METHODS: Genetic information from four subject groups was collected: non-dependent opioid users (NOD) [n=163]; opioid-dependent (OD) patients in methadone maintenance treatment (MMT) [n=143]; opioid-dependent MMT-resistant patients in heroin-assisted treatment (HAT) [n=138]; and healthy controls with no history of opioid use (HC) [n=153]. Eighty-two variants in eight opioid system genes were studied. To establish the role of these genes in (a) non-dependent opioid use, and (b) heroin dependence, the following groups were compared: HC vs. NOD; HC vs. OD (MMT+HAT); and NOD vs. OD (MMT+HAT). RESULTS: Five unique SNPs in four genes showed nominally significant associations with non-dependent opioid use and heroin dependence. The association of the delta opioid receptor (OPRD1) intronic SNP rs2236861 with non-dependent opioid use (HC vs. NOD) remained significant after correction for multiple testing (OR=0.032; p(corrected) = 0.015). This SNP exhibited a significant gene-gene interaction with prepronociceptin (PNOC) SNP rs2722897 (OR=5.24; p(corrected) = 0.041) (HC vs. NOD). CONCLUSIONS: This study identifies several new and some previously reported associations of variants with heroin dependence and with non-dependent opioid use, an important and difficult to obtain group not extensively studied previously. Further studies are warranted to confirm and elucidate the potential roles of these variants in the vulnerability to illicit drug use and drug addiction.